State Vs Individual in Christopher Greyson’s And Then She Was Gone - Gol Man Gurung (Interdisciplinary Journal of Management and Social Sciences, 2022)
The research examines state's subjugation of individual power and authority in Christopher Greyson's And Then She Was Gone. It introduces power theory and shows state's exercise of power and use of force against individual power. The state power defines law and authority which is mandatory and individual power exercise is punishable. As novel identifies a character who is professional spy however, he cannot define truth and justice which is state's perspective. Truth is no matter for state but it defines truth. The character fights for justice and truth but the state never accepts the justice from the perspective of state.